Effect of Moist Stratification (Warm, Cold & Warm + Cold) on Seed Germination Parameters of Ash (Fraxinus floribunda Wallich.) Tree - Mughal, A. H.; Shoaib, Raja (Indian Forester, 2010)
Laboratory study was conducted on one year seeds of Fraxinus floribunda during August 2006. In order to over come poor and slow germination due to dormancy, the seeds were first moistened for 48 hours for imbibition and thereafter subjected to (warm, cold and warm + cold) stratifications ranging from 1 to 4 week duration. Seeds thereafter were put to germination test in petri plates on germination paper at 20 Â± 2Â°C in seed germinator. Germination was recorded after 7 days and continued till 30th day. Results obtained indicated that F. floribunda has intermediate physiological dormancy and the same can be over come by cold stratification for a period of 4 weeks. Germination per cent, mean germination time and germination value were 78%, 16.42 days and 26.67 respectively after 4 weekofcoldstratification.